Effect of Supplemental Feeding on Winter Diet and Body Mass of Northern Bobwhites - Ryan E. Whitelaw; William E. Palmer; Shane D. Wellendorf; John P. Carroll (National Quail Symposium Proceedings, 2017)
Supplemental feeding by spreading grain is a common management practice on private lands managed for northern bobwhites (Colinus viginianus), but its effect on diet of bobwhites is not well documented. We examined crop contents from 160 northern bobwhites collected in January and February of 2002 and 2003 from Tall Timbers Research Station, Tallahassee, FL, and Pebble Hill Plantation, Thomasville, GA. Sorghum seed (Sorghum vulgare) was spread bi-weekly on approximately half of each study area along a dedicated feed trail through the cover. Dry mass of crop contents from harvested bobwhites averaged 2.51g (SE = 0.171) and was composed primarily of seeds ( Χ = 2.44 g; SE = 0.171), with minor invertebrate (Χ = 0.052g; SE = 0.021) and vegetation (Χ = 0.016g; SE = 0.004) matter. Dry mass of crop contents for bobwhites averaged 2.94 g (SE = 0.280) for birds from fed sites and 2.09g (SE = 0.187) from reference sites. On fed sites 67.5% of bobwhites had used sorghum and sorghum accounted 71% of food items by weight. Diet varied annually, primarily with changing use of acorn, (Quercus spp.) pine (Pinus spp.) mast, and partridge pea (Cassia spp.). Adult bobwhites captured in January averaged 169.9g (SE = 0.970; n = 181) on reference sites and 174.8g (SE = 0.896; n = 237) on fed sites. Supplemental feeding by spreading sorghum was an effective method of providing seeds with high metabolizable energy to bobwhites.
Keywords: Colinus virginianus; Florida; Georgia; milo; northern bobwhite; quail; Sorghum vulgare; supplemental feed